2011
DOI: 10.4028/www.scientific.net/amm.88-89.583
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Method of Hoisting Points Schemes Using Strain Energy Criterion

Abstract: The optimization method of hoisting point’s schemes using strain energy criterion was studied in this paper. Firstly, the finite element model of complex steel truss hoisting was established and optimization analysis of hoisting point’s schemes for complex steel truss hoisting using strain energy criterion was accomplished. The calculation code which can make finite element analysis and optimization analysis of lifting point’s schemes based on strain energy criterion automatically. Then, lifting point’s scheme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…Compared to prior research [19,20,23,24], the optimization outcomes presented in this paper offer more practical insights for engineering applications. These findings were derived from a simulation optimization approach that focused on identifying the most hazardous points during hoisting operations under actual working conditions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Compared to prior research [19,20,23,24], the optimization outcomes presented in this paper offer more practical insights for engineering applications. These findings were derived from a simulation optimization approach that focused on identifying the most hazardous points during hoisting operations under actual working conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The findings presented in Section 3.2 indicate the necessity for the hoisting design to undergo further optimization. Additionally, studies have demonstrated that differential lifting point designs can cause stress and strain changes during the hoisting process [19,22,23].…”
Section: Optimal Design Of Lifting Pointsmentioning
confidence: 99%
See 3 more Smart Citations